Microsoft Office XP basics - Morrison, Connie (Course Technology, 2002)
This text is ideal for a lower-level course on the new Microsoft Office XP integrated software. Though introductory in nature, the text comprehensively covers the most popular features of word processing, spreadsheets, databases, and much more!